Pearson's Hard-Soft Acid-Base Principle as a Means of Interpreting the Reactivity of Carbon Materials - M. Wiśniewski; P.A. Gauden (Adsorption Science & Technology)
In the current studies we are focusing on the utility of the theory of hard and soft acids and bases (HSAB), as proposed by Pearson, for the description of the reactivity of different types of two-radical graphene sheets where two neighbouring carbon atoms are unsaturated in the zigzag position. The closed- and open-shell systems were taken into account. The well-known theoretical reactivity indices (ionization potential, electron affinity and global softness) were calculated for the adsorbents analyzed. We have shown that the values of these parameters are independent of the size of the carbon models. To test the reactivity of adsorption sites as probe molecules, we have used the chloride anion (Cl − ), cation (Cl + ) and radical (Cl 0 ), respectively. Respective correlations between the enthalpy of reaction, the ionization and/or electronic chemical potential of the carbon structures were found. The results obtained confirm the original HSAB concept of Pearson which has been improved recently by Nalewajski. A similar relationship was observed for the adsorbent charge-transfer term, i.e. the change in the electron densities of the analyzed graphene sheets before and after the adsorption process. From an analysis of the results presented, it has been deduced that a charge-transfer mechanism is probable for chloride ion/adsorbent complexes. Moreover, the acid–base duality of carbon models during the adsorption process was shown and confirmed.